Long-term effects of group-based agricultural support amid COVID-19 shocks in Nepal - David A. Raitzer; Odbayar Batmunkh; Sakina Shibuya (Asian Development Bank (ADB), 2025)
This paper examines the long-term effects of agricultural support in western Nepal and whether support enhanced farmers' resilience to coronavirus disease (COVID-19) disruptions. From 2014 to 2022, farmers received various combinations of training, input (such as fertilizer and seed) subsidies, asset support, and credit, delivered through agricultural groups by multiple programs. Many of these programs had objectives related to the improvement of agricultural commercialization, which raises the question of whether they made households more vulnerable or resilient to market disruptions. We apply two-way fixed effects regressions and inverse probability weighting to estimate impacts of support from a 1,521 household panel dataset of observations in 2014, 2018, and 2022, which encompasses variations in both program exposure and local lockdown severity. We find that support led to substantial improvements in crop productivity, value, sales, and income. Effects are largest for support including training, asset subsidies, or credit, and support focused on higher-value products. Support provided between 2018 and 2022 had large effects in offsetting the negative impacts of COVID-19 restrictions, whereas support provided up to 2018 had a persistent effect in improving resilience to COVID-19 shocks. Effects from both periods of support are progressive with respect to income.
Keywords: O13; Q13; Q16; Q54; 330; Nepal; matching grants; extension; asset transfer; agriculture; COVID-19; resilience